Intermediary elites in the treaty port world : Tong Mow-chee and his collaborators in Shanghai, 1873–1897 - Abe, Kaori (2015)
This article examines the functions of Chinese and foreign intermediary elites in the commercial and political world of Shanghai, an international city in the nineteenth century mainly consisting of British, American, European and Chinese residents. Specifically, it focuses on the formation of the socio-economic network of Tong Mow-chee (Tang Maozhi 唐茂枝) (1828–1897), a well-known Chinese compradormerchant serving the British firm Jardine Matheson & Co. and other anglophone and Chinese figures, including William Venn Drummond and Tong King-sing who supported Mow-chee’s commercial and political activities. My research mainly draws on English and Chinese sources and enables a deeper understanding of the unofficial figures who contributed to the management of the international society of Shanghai in the late nineteenth century, offering new insight into social roles of the middlemen operating in an area of Britain’s informal empire in China.